Study on Correlations Between Glycated Haemoglobin, Lipid Profiles and Blood Glucose Levels in Type 2 Diabetics Living at Moderate High Altitude - B, Rajashekar Rao; PB, Parineetha; Vc, Venkata Raman (IIUM Medical Journal Malaysia, 2010)
Introduction: The study was conducted to look for the effects of polycythaemia on Glycosylated Haemoglobin (GHb) levels and to the see the correlations between the levels of haemoglobin, GHb, blood glucose, and lipid profiles including Atherogenic Index of plasma (AIP), in type 2 diabetics living 5800ft above sea level at Gangtok in Sikkim, India. GHb is used to predict the risk of long term complications of Diabetes mellitus (DM) like coronary artery disease (CAD). Materials and Methods: The study group consisted of Group I (Type 2 DM male patients with PPG levels 200mg/ dl) and age matched healthy males formed the control group. Results: In Group I, GHb levels correlated positively with AIP, but not with TC/HDL-C ratio. In Group II, both PPG and GHb levels correlated positively with Total cholesterol (TC), LDL Cholesterol, TC /HDL-C ratio and AIP. This shows that higher PPG levels are associated with more Atherogenic lipid profiles. Study also showed higher GHb levels in controls at 7.61%, and correlated positively with postprandial glucose (PPG) levels (r = 0.92). Conclusion: In predicting risk for future CAD, PPG levels and AIP can be used as an adjunct parameter.